2015
DOI: 10.1002/mas.21462
|View full text |Cite
|
Sign up to set email alerts
|

Applying mass spectrometry to study non‐covalent biomolecule complexes

Abstract: Non-covalent interactions are essential for the structural organization of biomacromolecules and play an important role in molecular recognition processes, such as the interactions between proteins, glycans, lipids, DNA, and RNA. Mass spectrometry (MS) is a powerful tool for studying of non-covalent interactions, due to the low sample consumption, high sensitivity, and label-free nature. Nowadays, native-ESI MS is heavily used in studies of non-covalent interactions and to understand the architecture of biomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 147 publications
0
71
0
Order By: Relevance
“…6 Electrospray ionization (ESI) allows the transfer of proteins and multi-protein complexes into the gas phase. [9][10][11][12] The resulting ions can be analyzed by mass spectrometry (MS), ion mobility spectrometry (IMS), and other gas phase techniques. [13][14][15][16][17][18][19][20] The question whether electrosprayed macromolecules retain their solution structures has attracted considerable attention.…”
mentioning
confidence: 99%
“…6 Electrospray ionization (ESI) allows the transfer of proteins and multi-protein complexes into the gas phase. [9][10][11][12] The resulting ions can be analyzed by mass spectrometry (MS), ion mobility spectrometry (IMS), and other gas phase techniques. [13][14][15][16][17][18][19][20] The question whether electrosprayed macromolecules retain their solution structures has attracted considerable attention.…”
mentioning
confidence: 99%
“…65 Chen and Gulbakan reported that the aptamer-protein interactions could also be studied by high resolution MALDI MS provided that sample preparation conditions were finetuned and -aza-2 thiothymine was used as the MALDI matrix. 66 …”
Section: Mass Spectrometry For Direct Characterization Of Aptamer-ligmentioning
confidence: 99%
“…UV and fluorescence spectroscopies and other spectroscopic methods can probe the structural changes of protein complexes based on the integral spectra for the analytes of interest, but are lacking in specific information of individual species and chemical stoichiometry. Native electrospray ionization mass spectrometry (native ESI‐MS) has proven to be a powerful tool for studying protein complexes, and it has been used to reveal the existence of noncovalent protein complexes and provide stoichiometric information and association constants . The affinity between proteins and drug molecule ligands is important for physiological and pathological processes, conducive to the development of new treatment methods for associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Native electrospray ionization mass spectrometry (native ESI-MS) has proven to be a powerful tool for studying protein complexes, and it has been used to reveal the existence of noncovalent protein complexes and provide stoichiometric information and association constants. [8][9][10][11][12][13][14] The affinity between proteins and drug molecule ligands is important for physiological and pathological processes, conducive to the development of new treatment methods for associated diseases.…”
mentioning
confidence: 99%